Strengthening Gastronomic Tourism in Surakarta City through a Google Earth-Based Tourism Route Model - Erna Sadiarti Budiningtyas; Yeremia Victor Rondonuwu (Research Horizon, 2026)
Besides being a city of culture, Surakarta is also known for its culinary delights. Many tourists come to Surakarta simply to enjoy its culinary delights. Recent developments in tourism have shifted tourist preferences beyond simply enjoying the culinary delights to gastronomic tourism. This study aims to identify the authentic gastronomy of Surakarta and develop a system for developing a gastronomic tourism itinerary in Surakarta, making it easier for tourists to plan their own gastronomic tourism itinerary. The research method employed a qualitative approach. Data collection involved tourists or food connoisseurs in Surakarta, cultural experts, tourism entrepreneurs, and tourism associations in Surakarta. Data collection used a questionnaire to determine tourist preferences for Surakarta’s gastronomy. This was followed by interviews with cultural experts, observation, and documentation. FGDs were conducted with several tourism organizations in Surakarta to obtain input on previous results. The results of this research provided data on authentic food, snacks, and restaurant locations that serve these dishes, which were then compiled into a web-based system that can be accessed by anyone in Surakarta City. The impact is a Surakarta gastronomic database that can be used as a guide for gastronomic tourists and can be developed for other destinations.